2021
DOI: 10.1128/aem.02867-20
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas Species from Nonchlorinated Distribution Systems and Their Competitive Planktonic Growth in Drinking Water

Abstract: Aeromonas is included in the Dutch Drinking Water Decree as an indicator for elevated microbial regrowth in non-chlorinated drinking water distribution systems (DWDS). The temporal and spatial diversity of Aeromonas species in ten DWDS and their planktonic growth characteristics for different carbon sources was investigated. Genotyping of the gyrB gene of isolates showed a non-systematic temporal and spatial variable prevalence of seven different Aeromonas species in these DWDS and no correlation with AOC-P17/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…A Percentages of virulence factors in different categories. B) Virulence genes in each virulence factor category drinking water and fresh water [2][3][4][5][6]. Human Aeromonas gastrointestinal infections most often occur in warm weather [1,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Percentages of virulence factors in different categories. B) Virulence genes in each virulence factor category drinking water and fresh water [2][3][4][5][6]. Human Aeromonas gastrointestinal infections most often occur in warm weather [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…Aeromonas veronii is a Gram-negative rod-shaped motile bacterium that inhabits mainly freshwater environments such as ground water, lakes and river [1]. It has also been isolated from chlorinated and untreated drinking water [2][3][4][5][6]. Several Aeromonas species including A. veronii are pathogens of aquatic animals, causing diseases such as skin ulceration and systemic hemorrhagic septicemia in fish, which is a great concern in aquaculture globally [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies of the feces of Asellus aquaticus have indicated that the feces leach organic acids, among other, biopolymers, which seems to support regrowth of bacteria [4,5].…”
Section: Macroinvertebrates As Hosts For Harmful Bacteriamentioning
confidence: 99%
“…The support that invertebrates provide for the survival and regrowth of microbes indicates the significance of these organisms to water quality and human health, as well as the need for continuous and quantitative monitoring of invertebrates. Invertebrate occurrence is one of the key parameters influencing microbial regrowth following treatment in addition to raw water quality, e.g., given by microbial growth, development of harmful bacteria as biome of invertebrates and jelly egg masses as substrate for microbe development [5,47,48].…”
Section: Proposed Activities For Biological Water Quality Control and Maintenancementioning
confidence: 99%
See 1 more Smart Citation